Analysis of the Role of Transformational Leadership Style on Employee Performance (Case Study at PT. BPRS Mojoartho Mojosari) - Alvina, Tahta; Fauziah, Nur Dinah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
Leadership style has a very important role in banking institutions because it greatly influences the work climate, the work climate in a company will affect the conditions, motivation, and work spirit of employees. This study aims to analyze the role of transformational leadership style on employee performance. In this study, the researcher used a qualitative case study, the location of this study was at PT. BPRS Mojoartho Mojosari. The data collection techniques used were observation, interviews, and documentation. The data analysis technique used was a triangulation of data sources. The results of this study indicate that the analysis of the role of transformational leadership style follows the characteristics of transformational leadership known as 4I, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. With this suitability, it can be said that the leader of PT. BPRS applies a transformational leadership style well. The motivation given by the leader of PT. BPRS Mojoartho Mojosari to his employees is to gives awards to employees who excel and promotions if they have worked for a long time and continue to provide good performance.